Cutaneous leishmaniasis in north Lebanon: re-emergence of an important neglected tropical disease. (21st May 2019) - El Safadi, Dima; Merhabi, Sabah; Rafei, Rayane; Mallat, Hassan; Hamze, Monzer; Acosta-Serrano, Alvaro
Abstract: Background: Cutaneous leishmaniasis (CL) is the most prevalent neglected tropical disease among externally displaced people in the Middle East. In recent years, the Lebanese population has increased >30%, mainly due to a mass influx of Syrian migrants, thousands of them carrying CL, among other infectious diseases. Here we revisit the current CL prevalence among refugees in northern Lebanon. Methods: This cohort study was conducted at the Al Bashaer Medical Center in north Lebanon between January and June 2017. A total of 48 randomly selected suspected CL patients were clinically diagnosed by dermatologists and samples were obtained for microscopic examination and molecular identification by polymerase chain reaction restriction fragment length polymorphism. The treatment response to antimonials was assessed each week and was followed for up 6 months. Results: Leishmania tropica was the predominant species (91.7%) followed by Leishmania major (8.3%). Confirmed cases were treated with one to two courses of antimonials and healing was usually achieved after receiving a second course of treatment. Importantly, we show evidence of possible local CL transmission by indigenous sandflies in three separate patients who had no history of recent travel to Syria. Conclusions: This highlights the urgent necessity to implement preventive disease strategies to avoid further dispersion of L. tropica CL in north Lebanon.